Síndrome da hipermobilidade articular em jovem - Joana Neves; Inês Cunha; Renata Aguiar; Anabela Barcelos (Sociedade Galega de Medicina Interna, 2016)
Joint hypermobility syndrome (JHS) is a hereditary connective tissue disorder characterized by symptomatic generalized joint hypermobility. Other features such as luxations and subluxations, periarticular lesions and cutaneous or other organ manifestations due to collagen defects are included in JHS clinical criteria. JHS may be clinically indistinct from Ehlers-Danlos syndrome hypermobility type (EDS). We report the case of a 14 year old male patient, with chronic low back pain and generalized joint hypermobility. He also presented a marfanoid habitus, hand joint alterations and striae in the right dorsal region. He fulfilled the Brighton Criteria therefore, after excluding other connective tissue diseases, the diagnosis of JHS was established. JHS is an underestimated and underdiagnosed disease, and must be contemplated in front of musculoskeletal pain associated with generalized hypermobility. The authors describe this case highlighting the importance of looking for signs and symptoms which allow the earlier diagnosis and management.